Gender, Discontinued Careers and Low Activity Rates in a Long Life Society - Sarfati, Hedva (Relations industrielles / Industrial Relations, 2004)
While long life society constitutes progress in terms of healthier, better and longer lives, it is also associated with higher pension and health expenditures to an extent that threatens the long term adequacy and sustainability of existing welfare systems. It therefore requires adaptation on the part of society and of social institutions and policies, in particular the labour market and the welfare systems, in order to stem or even reduce the growing dependency ratios of the population. In this context, the gender dimension is crucial for any policies that aim at improving the effectiveness of labour markets and social and economic inclusion. This article thus starts by signalling the six main changes that have occurred in the European Union and US labour markets and the workforce, which concern in particular women in all age groups. It then highlights the main responses of the welfare systems to these changes, emphasizing activation measures and indicating their successes and shortcomings—as illustrated by the Danish and UK experience. The article concludes by suggesting policies that may enhance female activity and employment rates, from both the labour supply and demand perspectives.